2006
DOI: 10.1590/s0100-879x2006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cyclosporin and sirolimus blood concentrations regarding the incidence and severity of hyperlipidemia after kidney transplantation

Abstract: The influence of drug concentrations on the development of persistent posttransplant hyperlipidemia was investigated in 82 patients who received cyclosporin A (CsA) and prednisone plus sirolimus (SRL) (52) or azathioprine (AZA) (30) during the first year after transplantation. Blood levels of CsA and SRL, daily doses of AZA and prednisone, and cholesterol, triglyceride, and glucose concentrations were determined during each visit (pretransplant and 30, 60, 90, 120, 180, and 360 days posttransplant). Persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Two patients each had one sirolimus concentration >15 ng/mL (Figure ). Neither patient developed hypertriglyceridemia, which has been shown in previous studies to be correlated with elevated sirolimus serum concentrations . One patient experienced an increase in serum creatinine (from 0.95 to 1.32 mg/dL) the day following the elevated sirolimus serum concentration.…”
Section: Resultsmentioning
confidence: 56%
“…Two patients each had one sirolimus concentration >15 ng/mL (Figure ). Neither patient developed hypertriglyceridemia, which has been shown in previous studies to be correlated with elevated sirolimus serum concentrations . One patient experienced an increase in serum creatinine (from 0.95 to 1.32 mg/dL) the day following the elevated sirolimus serum concentration.…”
Section: Resultsmentioning
confidence: 56%
“…In contrast, other studies show a dose or trough dependence of sirolimus-induced hypertriglyceridemia. 8,9 Spinelli et al reported that triglyceride concentration was independently associated with sirolimus level (r 2 ¼ .03, P ¼ .005) regardless of cyclosporine level. 9 They concluded that sirolimus-induced hypertriglyceridemia was dependent on sirolimus level.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition to all of the risk factors of the general population, the presence of impaired allograft function, proteinuria, an acute rejection episode and its treatment with corticosteroids, new-onset diabetes mellitus after transplantation and various types and doses of immunosuppressive agents also contribute as risk factors among the kidney transplant population. 3,4 Several guidelines defining the type, severity, and targets for therapeutic interventions of dyslipidemia have been implemented. They focus on total cholesterol (TC) and/or low-density lipoprotein cholesterol (LDL-C) concentrations.…”
mentioning
confidence: 99%